Oggi la città Riflessione sui fenomeni di trasformazione urbana - Capestro, Antonio (Strumenti per la didattica e la ricerca, 2012)
Today the city is experiencing new forms of urban culture, between cityscape and mindscape. The cityscape moulded through tangible forms and values, spatialized in architectural and urban layouts, is increasingly linked to a mindscape project which originates from intangible forms and values linked to interests, events, invention and enhancement of resources in continuous movement. The cityscape advanced in this sense can but be planned together with a mindscape that is heterogeneous and complex and increasingly based on the experience that the place can offer. In it event and permanency blend to construct a personalized urban tale that puts the principle of utility alongside that of the desire to become a geographical-spatial, but also existential, landscape. This book reflects on the dynamics of the transformations caused by new forms of production and exchange in order to note down topics to apply to town planning.